Development of Tea Exports in West Java Through Global Cooperation and Sustainable Innovation - Rizal Saefuloh; Pupu Fujiah; Melza Oktaviani; Silvia Hanif Alvianita; Fajar Lazman (INDIEGO: Indonesian Journal of Diplomacy, Political & Economical for Global Society, 2025)
This research examines the development of tea exports in West Java through global cooperation and sustainable innovation. With a contribution of 67.6% of total national tea production, West Java has a strategic role in the Indonesian tea industry. Using qualitative methods with a literature study approach and in-depth interviews, this research analyzes export development strategies, challenges faced, and collaboration between stakeholders. The research results show that the development of West Java tea exports is supported by three main strategies: strengthening export marketing networks, trade promotion programs, and business digitalization. Innovation and product diversification, such as the development of artisan tea and health products, are key to increasing competitiveness. Despite facing challenges in the form of high certification standards and global competition, collaboration is effective between stakeholder as well as government support through facilitating certification and developing market intelligence contribute to overcoming these obstacles. This research provides recommendations for strengthening the competitiveness of West Java tea exports through improving technology, developing human resources, and expanding markets.